Diagnosis of oral manifestations in HIV/AIDS patients who used HAART and developed diabetes mellitus - Adam de Mello Silva; Camila Correia dos Santos; Elcio Magdalena Giovani (Universidade Estadual de Campinas, 2015)
Aim: To assess the prevalence of oral manifestations in HIV/AIDS patients and a possible correlation of the development of diabetes mellitus due to highly active antiretroviral therapy (HAART). Methods: 56 patients were examined, divided into two groups, Group 1, the HIV group, with 28 patients known to be HIV+, who developed diabetes mellitus due to HAART, and Group 2, the control group, with 28 patients with HIV- diagnosed with diabetes mellitus. Results: In Group 1, normal salivary flow rate and buffering capacity were observed in 18 (64.3%) patients, but the bleeding index high (46.53%) and higher incidence of periodontal disease was found in this group. In Group 2, 11 (39.2%) and 15 (53.5%) patients had low and normal salivary flow rate, respectively. High T-CD4 indices with mean value of 22.46 for each patient, showing xerostomia in 9 (32.1%) patients and dental caries in 11 (39.3%). Conclusions: Regarding the oral and general manifestations, the HIV group showed higher rates of pathologies when compared with the control group. The HIV group and the control group were diagnosed with diabetes, but this condition in the HIV group presented earlier than in the control group, suggesting a possible association with HAART.